2021
DOI: 10.1182/bloodadvances.2020003526
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic factors in adolescents and young adults with ALL treated with a modified BFM-90 protocol

Abstract: The use of pediatrics-inspired protocols in adolescent and young adult (AYA) acute lymphoblastic leukemia (ALL) results in superior survival compared with the adult protocols. Pediatrics-inspired protocols carry an increased risk of toxicity and treatment-related mortality in low resource settings, which can offset the potential benefits. We studied the outcomes and prognostic factors in the treatment of AYA ALL with a pediatrics-inspired regimen. We retrieved data regarding demographics, investigations, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…Although these are much higher than other studies using rituximab in ALL, a very similar trend has been seen in our patients undergoing induction therapy for acute leukemia and adolescent and young adult ALL. 18,21,22 Higher infection rates compared with the reported literature did not increase induction mortality than the reported literature (3%-7%). 11,12,25 We observed no grade 3 or higher neuropathy despite combining 2 potentially neurotoxic drugs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although these are much higher than other studies using rituximab in ALL, a very similar trend has been seen in our patients undergoing induction therapy for acute leukemia and adolescent and young adult ALL. 18,21,22 Higher infection rates compared with the reported literature did not increase induction mortality than the reported literature (3%-7%). 11,12,25 We observed no grade 3 or higher neuropathy despite combining 2 potentially neurotoxic drugs.…”
Section: Discussionmentioning
confidence: 51%
“…All patients received the modified BFM-90 protocol, 21 with no highrisk blocks of chemotherapy. Rituximab was given as an intravenous infusion at a dose of 375 mg/m 2 of body surface area, once weekly for 5 doses during induction (on days 1, 8, 15, 22, and 28).…”
Section: Treatment and Proceduresmentioning
confidence: 99%
“…Beyond discussions about the definition of the AYA age group, we were not able to identify any papers specifically dedicated to allogeneic HSCT in an AYA ALL population. Published ALL studies reported overall results of ALL therapy in this population but did not necessarily disclose how an AYA group was defined, state whether there were any adjustments in the HSCT indications for this group compared with indications for children or adults, or address HSCT results specifically in AYAs ( 15 , 20 ). In paediatric studies, AYAs are often limited to 18–21-year-old patients and results are not provided for older AYAs ( 20 ).…”
Section: Indication For Hsctmentioning
confidence: 99%
“…Published ALL studies reported overall results of ALL therapy in this population but did not necessarily disclose how an AYA group was defined, state whether there were any adjustments in the HSCT indications for this group compared with indications for children or adults, or address HSCT results specifically in AYAs ( 15 , 20 ). In paediatric studies, AYAs are often limited to 18–21-year-old patients and results are not provided for older AYAs ( 20 ). In adult studies, AYAs are usually included in the overall cohort along with 40–60 years old patients; this probably worsen their outcome vs. if the older patients were studied separately.…”
Section: Indication For Hsctmentioning
confidence: 99%
“…Most referral institutions in the country are now transitioning towards paediatric‐inspired protocols for the treatment of ALL in the adolescent and young adult group of patients. A recent systematic review and large retrospective studies indicate this transition in treatments 27,37 . This has also been facilitated by an increasing crosstalk and collaboration occurring between adult and paediatric haemato‐oncology physicians within and outside their respective institutions.…”
Section: The Perspective From India (Vs Radhakrishnan and M Chandy)mentioning
confidence: 99%